Addition of Mycobacterium indicus pranii vaccine as an immunotherapeutic to standard chemotherapy in borderline leprosy: a double‐blind study to assess clinical improvement (preliminary report). (7th April 2017) - Kamal, R.; Pathak, V.; Kumari, A.; Natrajan, M.; Katoch, K.; Kar, H.K.
Abstract : Respond to this article